TINJAUAN YURIDIS TIDAK DITAHANNYA TERSANGKA BERDASARKAN PASAL 21 KUHAP DALAM PROSES PENYIDIKAN - Aliful Anhar (2024)
Indonesia operates under a legal framework that governs its society through established laws. It predominantly follows positive law, categorized into public and private law. Public law encompasses criminal law, which regulates interactions between the public and the state. The Criminal Code delineates prohibitions and sanctions, while the Code of Criminal Procedure (KUHAP) outlines procedural mechanisms. Detention, a coercive measure during investigations, is authorized under specific conditions outlined in the Code of Criminal Procedure. Investigators exercise subjective judgment during detention, necessitating clarity on limitations and regulatory foundations. The study adopts a normative juridical approach with a statutory focus. It underscores the absence of cooperation as a detention condition and advocates for adhering to both objective and subjective conditions for legal certainty in the detention process.